Pola Konsumsi Protein Hewani Dan Lemak Sebagai Faktor Risiko Kejadian Kanker ServiksPola Konsumsi Protein Hewani Dan Lemak Sebagai Faktor Risiko Kejadian Kanker Serviks - Ni Putu Ari Oktaviani Sukmadewi; Lely Cintari; Ni Komang Wiardani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Cervical cancer that arise due to the growth of abnormal tissue cells attack the cervix. Cervical cancer ranks second most among women in Indonesia with an average death of 23.4 per 100,000 population. One factor that causes cervical cancer is the consumption pattern of animal protein and fat. The purpose of this study was to determine patterns of consumption of animal protein and fat as risk factors for cervical cancer in Wangaya Denpasar Hospital. This type of research is a case control conducted in January-March 2020. The population of the case study was all female patients suffering from cervical cancer in the Wangaya Denpasar Hospital Welfare Clinic with 10 subjects and 10 controls. This sampling technique with non-probability random sampling technique is the purposive method. Analysis of the data used by using the Chi-Square statistical test and Odds Ratio. Based on the results of statistical tests found a significant relationship between the amount of animal protein with cervical cancer incidence (p = 0.04), there is no significant relationship between the type and frequency of animal protein with cervical cancer incidence (p1 = 0.063, p2 = 0.064). Significant relationship between types of fat with cervical cancer incidence (p = 0.03), there is no significant relationship between the amount and frequency of fat with cervical cancer incidence (p1 = 0.154, p2 = 0.36). The amount, type and frequency of animal protein has no risk of cervical cancer, nor does the amount, type and frequency of fat have a risk of cervical cancer.Keywords: consumption patterns of fat and protein of animals, cervical cancer, risk factors